Cluster randomized controlled trial of a mobile market intervention to increase fruit and vegetable intake among adults in lower-income communities in North Carolina - Lucia A. Leone; Gina L. Tripicchio; Lindsey Haynes-Maslow; Jared McGuirt; Jacqueline S. Grady Smith; Janelle Armstrong-Brown; Ziya Gizlice; Alice Ammerman (BMC, 2018)
Abstract Background Poorer diets and subsequent higher rates of chronic disease among lower-income individuals may be partially attributed to reduced access to fresh fruits and vegetables (F&V) and other healthy foods. Mobile markets are an increasingly popular method for providing access to F&V in underserved communities, but evaluation efforts are limited. The purpose of this study was to determine the impact of Veggie Van (VV), a mobile produce market, on F&V intake in lower-income communities using a group randomized controlled trial. Methods VV is a mobile produce market that sells reduced-cost locally grown produce and offers nutrition and cooking education. We recruited 12 sites in lower-income communities in North Carolina (USA) to host VV, randomizing them to receive VV immediately (intervention) or after the 6-month study period (delayed intervention control). Participants at each site completed baseline and follow-up surveys including F&V intake, perceived access to fresh F&V and self-efficacy for purchasing, preparing and eating F&V. We used multiple linear regression to calculate adjusted differences in outcomes while controlling for baseline values, education and clustering within site. Results Among 142 participants who completed the follow-up, baseline F&V intake was 3.48 cups/day for control and 3.33 for intervention. At follow-up, adjusted change in F&V consumption was 0.95 cups/day greater for intervention participants (p = 0.005), but was attenuated to 0.51 cups per day (p = 0.11) after removing extreme values. VV customers increased their F&V consumption by 0.41 cups/day (n = 30) compared to a 0.25 cups/day decrease for 111 non-customers (p = 0.04). Intervention participants did not show significant improvements in perceived access to fresh F&V, but increased their self-efficacy for working more F&V into snacks (p = 0.02), making up a vegetable dish with what they had on hand (p = 0.03), and cooking vegetables in a way that is appealing to their family (p = 0.048). Conclusions Mobile markets may help improve F&V intake in lower-income communities. Trial registration Clinicaltrials.gov ID# NCT03026608 retrospectively registered January 2, 2017.